A note on connectedness in intuitionistic fuzzy special topological spaces - Selma Özçağ; Doğan Çoker (International Journal of Mathematics and Mathematical Sciences)
We prove some properties of several types of connectedness defined in intuitionistic fuzzy special topological spaces.